2015
DOI: 10.1155/2015/865083
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vitreomacular Adhesion on Age-Related Macular Degeneration

Abstract: Herein, we review the association between vitreomacular adhesion (VMA) and neovascular age-related macular degeneration (AMD). Meta-analyses have shown that eyes with neovascular AMD are twice as likely to have VMA as normal eyes. VMA in neovascular AMD may induce inflammation, macular traction, decrease in oxygenation, sequestering of vascular endothelial growth factor (VEGF), and other cytokines or may directly stimulate VEGF production. VMA may also interfere with the treatment effects of anti-VEGF therapy,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 68 publications
(87 reference statements)
0
8
0
1
Order By: Relevance
“…In other words, ERM alone, which is associated with tangential traction without AP traction, may not affect choroidal thickness. A recent study showed decreased choroidal thickness at 3 months after vitrectomy with ILM peeling (Kang & Koh ). However, the sample size in the study was small (21 eyes in 21 patients), and the presence or absence of VMT was not described.…”
Section: Discussionmentioning
confidence: 96%
“…In other words, ERM alone, which is associated with tangential traction without AP traction, may not affect choroidal thickness. A recent study showed decreased choroidal thickness at 3 months after vitrectomy with ILM peeling (Kang & Koh ). However, the sample size in the study was small (21 eyes in 21 patients), and the presence or absence of VMT was not described.…”
Section: Discussionmentioning
confidence: 96%
“…According to Newton's third law (every action has an equal and opposite reaction), the anteroposterior traction on the retina can affect the retinal pigment epithelium (RPE) and choroid, as has been described by Stefansson (Stefansson 2009). However, they only measured choroidal thickness by manual assessment (Kang & Koh 2015). A rise of VEGF leads to hyperpermeability of the membranes and choroidal rearrangement (Kinoshita et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In recent studies, Kang & Koh have described decreased choroidal thickness after vitrectomy, with ILM peeling. However, they only measured choroidal thickness by manual assessment (Kang & Koh 2015). Another factor that cannot be ignored is the vitreous oxygenation status after vitrectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Предполага-ют, что плотный контакт задней гиалоидной мем-браны с поверхностью сетчатки не только создает предпосылки для механических тракций, что запу-скает хроническое воспаление и оксидативный стресс, но и ухудшает оксигенацию сетчатки. Кроме того, существует мнение, что стекловидное тело мо-жет выступать в роли депо провоспалительных и ан-гиогенных факторов, способствуя снижению эф-фективности антиангиогенной терапии [10]. Со-гласно классификации The International Vitreomacular Traction Study group 2013 г., ВМА определяется как наличие контакта стекловидного тела с сетчат-кой в пределах области вокруг фовеа радиусом 3 мм в сочетании с отделением задней гиалоидной мем-браны от сетчатки в смежных областях при отсут-ствии каких-либо изменений профиля сетчатки [11].…”
Section: рис 8 окт-признаки надвигающейся га у пациентов с мягкими unclassified